PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH (SAP), PENGETAHUAN PENGELOLA DAN KETERSEDIAAN SARANA PRASARANA TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Pada SKPD di Kabupaten Kuantan Singingi) - Dewi Sartika; Zulbahridar -; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to test the effect of the application of accounting standards related to the government, the management of knowledge and the availability of infrastructure to the quality of the financial statements in the local government district Singingi strength. Data was collected by distributing questionnaires to the respondents. The population used in this study is a staff / staff involved in the preparation of the budget, the number of samples taken by 84 people and the samples can be processed. The data analysis technique used to test the hypothesis of the research is multiple linear regression analysis using SPSS softwareversion20.0. These results indicate two variables affect the quality of financial reports and only one variable that does not have an influence on the quality of financial reporting. Two variables that affect the application of accounting standards (SAP), and knowledge managers. While the availability of infrastructure had no effect on the quality of the financial statements.Keywords: government's application of accounting standards (SAP), knowledge managers, facility infrastructures, and quality of financial reporting.